Segmenting visitors' motivation, price perceptions, willingness to pay and price sensitivity in a collaborative destination marketing effort. Issue 21 (1st November 2020) - Stangl, Brigitte; Prayag, Girish; Polster, Lisa
ABSTRACT: While several studies segment the motives of travellers, the relationship between these segments, and the travellers' price perceptions, their willingness to pay (WTP), and price sensitivity remains scantly researched. Applying a neural gas algorithm to segment the travel motives of 714 visitors to Langenfeld, Austria, reveals the existence of three motivation clusters that are different in terms of the minimum, maximum and fair prices that travellers are willing to pay. Also, based on four self-assembled holiday packages offered as part of a collaborative destination marketing effort by different providers in Langenfeld, we demonstrate that visitors are willing to pay different prices for the selected packages and this has an influence on profitability of the destination. Implications for destination marketing and pricing strategies are offered.